2011
DOI: 10.1002/pam.20618
|View full text |Cite
|
Sign up to set email alerts
|

Energy demand‐side management: New perspectives for a new era

Abstract: Over the past decade and a half, state governments have assumed greater responsibility over demand-side management (DSM) operations. Whereas DSM programs formerly were initiated primarily by utilities or state public utility commissions, they are now becoming increasingly state-initiated and incentivized through funding mechanisms or efficiency-level mandates. The supporting literature, however, has yet to respond to these changes and to verify that DSM funding or mandates are effective policy mechanisms. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The research approaches were used to evaluate the implementation of current energy efficiency policies that have already been adopted. A primary focus in this sector of energy policy is Energy Efficiency Resource Standards (e.g., Carley, , ; Carley & Browne, ). These standards require utilities to reduce anticipated load with energy efficiency measures and are mainly adopted at the state level.…”
Section: Energy Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The research approaches were used to evaluate the implementation of current energy efficiency policies that have already been adopted. A primary focus in this sector of energy policy is Energy Efficiency Resource Standards (e.g., Carley, , ; Carley & Browne, ). These standards require utilities to reduce anticipated load with energy efficiency measures and are mainly adopted at the state level.…”
Section: Energy Efficiencymentioning
confidence: 99%
“…This support is crucial, as renewables are currently still on the periphery of the overall energy transmission infrastructure. Ideology at the citizen and the governmental level also plays a crucial role in determining the effectiveness of RPS (Carley & Miller, ). For standards that were stringent and strictly enforced, the governmental ideology drove policy adoption, whereas standards that were voluntary reflected an influence from citizen‐level ideologies (Carley & Miller, ).…”
Section: Renewable Energymentioning
confidence: 99%
“…Consumer demand management plays a vital role in power system stability. This can be done through planning, monitoring, and by implementing different techniques at the supplier as well as at the consumer end [43][44][45][46][47][48][49][50][51].…”
Section: Our Proposed Surveymentioning
confidence: 99%
“…These PBFs have been largely introduced into state energy strategies to combat decreased funding for public‐purpose and innovative clean energy programs brought about by electricity deregulation (Nadel & Kushler ). Despite the prevalence of PBFs across the United States, previous research has focused mostly on other policy instruments such as a renewable portfolio standard (RPS) and tax incentive programs, leaving a gap in knowledge and a need for further research on PBFs (Carley & Browne , Carley ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies by the American Council for an Energy‐Efficient Economy found PBFs to be cost‐effective tools for promoting energy efficiency and achieving significant electricity savings (Kushler et al , Nadel & Kushler ). One study modeled electricity savings to find that PBF programs have a significantly positive effect on utility energy efficiency investments when coupled with other performance incentives; utilities can use PBF money to cover some upfront project costs and then later earn a rate of return on their investments or receive rewards for meeting efficiency goals (Carley ). Two different studies examined the impact of PBFs on renewable energy, assessing whether the presence of a state PBF is associated with growth in wind energy generation (Adelaja et al , Menz & Vachon ).…”
Section: Introductionmentioning
confidence: 99%